Budgeting in Austria - Downes, Ronnie (OECD Publishing, 2018)
Over the past decade Austria has undertaken a carefully-considered and ambitious series of modern budgeting reforms. Evaluation of the budget reforms was purposely built into the reform process. The budget law provides for an external evaluation no later than 2017. To meet these obligations, Austria's Federal Ministry of Finance (Bundesministerium für Finanzen, BMF) set in place a comprehensive evaluation process in three parts during 2017. A first review conducted by the IMF focused on fiscal transparency. This second review, carried out by the OECD, covers budgetary management, performance budgeting and related issues. A third review by the Alpen- Adria University is focused on the financial management and reporting system including accrual accounting; as well as preparation of a synthesis report drawing upon the three stand-alone studies. The external evaluation exercises come after an internal evaluation conducted by the BMF which has considered several of these topics; some reforms have already been implemented, or are now underway, on foot of that internal review. JEL codes: H50, H61, H83 Keywords: Budget reforms, performance, impact assessment, financial management, transparency, cash and accruals financial reporting